PENINGKATAN HASIL BELAJAR IPA MATERI TEMPAT HIDUP MAKHLUK HIDUP MELALUI PEMBELAJARAN AKTIF TIPE CARD SORT DI KELAS II SDN KETAWANG KARAY I KEC. GANDING KAB. SUMENEP SEMESTER 1 TAHUN PELAJARAN 2018/2019 - Sayuti, Sayuti (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
The background of the research was that the learning outcomes of science students in class II were still low, namely under KKM 70, out of 14 students only 5 students (36%) completed while 9 students (64%) had not yet finished. This research was conducted to improve learning outcomes of students in science learning material where living things in class II Ketawang Karay I SDN Ganding Subdistrict Sumenep Regency 1st Semester 2018/2019 through the Card Sort Type Active Learning Strategy. This research was conducted on second grade students of Ketawang Karay I Elementary School in Ganding Subdistrict, Sumenep Regency during science learning with living things using living things using the Card Sort Type Active Learning Strategy. The action plan in this study will be carried out in 2 cycles and is planned to be carried out with steps of planning, action, observation, and reflection. The results showed that in the pre-cycle, the condition of student learning outcomes had not been satisfactory, there were only 36% or 5 new students completed in learning and the remaining 9 people or about 64% of students who had not completed the classical average of 47. So that repairs are continued by explaining and using the learning steps with an active learning strategy type card sort. In the first cycle there was an increase in student learning outcomes that was quite good, where there were 9 students or about 64% who completed the learning and the remaining 5 students or about 36% of students who have not completed the classical average of 73. Then in the second cycle, the learning outcomes of students experienced a very significant increase in which 14 students all completed or 100% in learning with a classical average of 87. This shows that using the Card Sort type active learning strategies can improve learning outcomes students in science learning in class II Ketawang Karay I Elementary School Ganding District Sumenep Regency.